EPICC study: evaluation of pharmaceutical intervention in cancer care. (16th January 2015) - Vantard, N.; Ranchon, F.; Schwiertz, V.; Gourc, C.; Gauthier, N.; Guedat, M.‐G.; He, S.; Kiouris, E.; Alloux, C.; You, B.; Souquet, P.‐J.; Freyer, G.; et al.
Summary What is known and objectives In cancer care, clinical pharmacists contribute to improving prevention and management of drug‐related problems (DRPs). The 3‐year EPICC study (Evaluation of Pharmaceutical Intervention in Cancer Care) aimed to collect and analyse pharmaceutical interventions (PIs) in oncology. Methods The free online version of the French Society of Clinical Pharmacy (SFPC) coding system, ACT‐IP, was used, supplemented by a standardized dedicated cancer‐care decision tree. Results A total of 29 589 medication orders (77 004 anticancer drug preparations) were analysed. Eight hundred and ninety‐four PIs were recorded. ACT‐IP identified 54·1% of DRPs as concerning over‐ or underdosage. The standardized dedicated cancer‐care decision tree identified the three principal causes of dosage problems: 50·2% due to miscalculation, 20% to omission of dose adjustment and 12% to poor choice of antineoplastic regimen. About 13·8% of DRPs were adverse effects and 3·9% were drug–drug interactions. The decision tree showed that 22% of adverse events could be circumvented by a switch within the same drug family and 72% of drug–drug interactions would have led to increased neoplastic toxicity. Discussion Pharmaceutical analysis of prescription forms contributes to medication safety in cancer care, and the present dedicated decision tree highlights additional information about DRPs and PIs. The DRP rate (3% of prescriptions) was consistent with the literature. The pharmacist has a role to play in optimizing the management of patients with cancer in terms of dose adjustment, drug toxicity management, improvement of administration and drug–drug interactions. What is new and conclusion This study, highlighting PIs in cancer care, is the first of this scale in terms of number of prescriptions analysed (nearly 30 000). Results demonstrated the specificity of DRPs and PIs for patients with cancer and the value of a dedicated coding system in cancer care.